2022
DOI: 10.1155/2022/6197638
|View full text |Cite|
|
Sign up to set email alerts
|

Security and Privacy Protection of Internet of Vehicles Consensus Algorithm Based on Wireless Sensors

Abstract: Due to its large network scale, open communication environment, unstable wireless network, and other characteristics, it is extremely vulnerable to attacks and causes security problems, resulting in the collapse of the Internet of Vehicles system. The application of the Internet of Vehicles is becoming more and more extensive, but there are still problems such as information security and privacy leakage in the Internet of Vehicles. Through the analysis of the security threats and privacy protection requirement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Wireless Communications and Mobile Computing has retracted the article titled "Security and Privacy Protection of Internet of Vehicles Consensus Algorithm Based on Wireless Sensors" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], significant concerns were identified with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%
“…Wireless Communications and Mobile Computing has retracted the article titled "Security and Privacy Protection of Internet of Vehicles Consensus Algorithm Based on Wireless Sensors" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], significant concerns were identified with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%